Single-Pill Combination Therapy for the Treatment of Severe Hypertension - Neutel, Joel M. (MD Conference Express, 2010)
Single-pill combination of telmisartan 80 mg/amplodipine 10 mg is superior to telmisartan or amlodipine monotherapy with regards to blood pressure reduction in patients with severe hypertension. This article discusses the findings from the TEAMSTA severe hypertension study.